Physicochemical, rheological and microstructural properties of Nano-Silica modified Bio-Asphalt - Al-Sabaeei, A.M. (Elsevier Ltd, 2021)
For its renewability, environmentally friendly and cost-effective advantages, bio-oil is employed to partially substitute the petroleum-based asphalt. However, its usage weakens the high-temperature performance of petroleum asphalt. Therefore, hydrophobic nanosilica (NS) particles were employed as a physical modifier of crude palm oil (CPO) to improve the high-temperature performance of bio-asphalt. CPO with the addition of 0, 5, 10 and 15 (by weight) and NS with the addition of 0, 2, 4 and 6 were used to obtain the NS-modified bio-asphalts. The chemical reaction between NS and CPO was evaluated by employing the Fourier-transform infrared spectroscopy (FTIR). Penetration and softening point tests were conducted to ensure the consistency, while dynamic shear viscosity, temperature sweep test, multiple stress creep recovery (MSCR) were employed to evaluate the high-temperature rheological performance of the bio-asphalts and NS-modified bio-asphalts. Moreover, the chemical functional groups and morphological characteristics of the selected NS-modified bio-asphalts were investigated using FTIR and Field emission scanning electron microscope (FESEM) tests. Test results show that the consistency of the NS-modified bio-asphalts was improved by reducing penetration, and increasing the softening points and dynamic viscosity. The NS particles increased the rutting parameter (G*/sinÎ´) and reduced the aging sensitivity of bio-asphalt, while decreased its permanent strain and non-recoverable creep compliance (Jnr), and improved the percentage of the recovery. FTIR analysis showed a chemical reaction that occurred due to the addition of bio-oil and NS into asphalt. Apart from that, the FESEM exhibited that NS was uniformly dispersed in the base and bio-asphaltsâ matrix. Therefore, NS effectively improved the high-temperature performance, aging resistance of the bio-asphalt. Â© 2021 Elsevier Ltd